2003
DOI: 10.1074/jbc.m307245200
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the Myocyte Enhancer Factor-2 Repressor Histone Deacetylase-5 by Endogenous Ca2//Calmodulin-dependent Kinase II Promotes Depolarization-mediated Cerebellar Granule Neuron Survival

Abstract: Cerebellar granule neuron (CGN) survival depends on activity of the myocyte enhancer factor-2 (MEF2) transcription factors. Neuronal MEF2 activity is regulated by depolarization via a mechanism that is presently unclear. Here, we show that depolarization-mediated MEF2 activity and CGN survival are compromised by overexpression of the MEF2 repressor histone deacetylase-5 (HDAC5). Furthermore, removal of depolarization induced rapid cytoplasm-to-nuclear translocation of endogenous HDAC5. This effect was mimicked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
99
2
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(109 citation statements)
references
References 60 publications
6
99
2
2
Order By: Relevance
“…Chronic stress induces NMDARdependent synaptic plasticity in the NAc (Belujon and Grace, 2011;Jiang et al, 2013) as well as plasticity of NAc synaptic structures (Christoffel et al, 2011), and both of these processes have been shown to involve CaMKII in various contexts (Colbran and Brown, 2004;Huang and Hsu, 2012;Robison et al, 2013). However, as CaMKIIa is present throughout the cell and is known to regulate histone modification machinery itself (Linseman et al, 2003), speculation for a specifically synaptic role for the fluoxetine-mediated reduction in CaMKIIa expression is premature.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic stress induces NMDARdependent synaptic plasticity in the NAc (Belujon and Grace, 2011;Jiang et al, 2013) as well as plasticity of NAc synaptic structures (Christoffel et al, 2011), and both of these processes have been shown to involve CaMKII in various contexts (Colbran and Brown, 2004;Huang and Hsu, 2012;Robison et al, 2013). However, as CaMKIIa is present throughout the cell and is known to regulate histone modification machinery itself (Linseman et al, 2003), speculation for a specifically synaptic role for the fluoxetine-mediated reduction in CaMKIIa expression is premature.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present work further substantiate HDAC4 as a specific direct substrate of CaMKIIā¦, based on the finding that HDAC4 phosphorylation was abolished in cardiac extracts from CaMKIIā¦-KO mice, whereas HDAC5 phosphorylation was unaffected. Others have reported that CaMKII induces cytosolic accumulation of both HDAC4 and HDAC5 (19,37,38). Because HDAC5 can acquire CaMKII responsiveness by oligomerization with HDAC4 (20), the nuclear export of HDAC5 in response to CaMKII signaling may reflect, at least in part, this type of indirect mechanism of HDAC5 regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that the phosphorylation of HDAC5 can be regulated by Ca 2+ /calmodulin-dependent kinase II (CaMKII) activity in neurons (11) and by protein kinase D (PKD) in other cell types (18). To determine whether HDAC5 phosphorylation in response to ketamine is mediated by CaMKII and PKD in hippocampal neurons, we treated cells with the CaMKII inhibitor KN-62 and PKD-specific inhibitor Gƶ6976.…”
Section: Resultsmentioning
confidence: 99%
“…HDAC5 is highly enriched in the brain with strong expression in forebrain regions including the hippocampus, cortex, and amygdala (9). We focus here on HDAC5 because its subcellular localization is tightly regulated by neuronal activity (11)(12)(13). The class II HDAC family of transcriptional repressors, in particular HDAC5, interacts with myocyte enhancer factor 2 (MEF2) to repress target gene expression (13,14).…”
mentioning
confidence: 99%